Programmable DNA-mediated decision maker - Shu, Jian-Jun (2017)
DNA-mediated computing is a novel technology that seeks to capitalise on the enormous informational capacity of DNA and has tremendous computational ability to compete with the current silicon-mediated computing, due to massive parallelism and unique characteristics inherent in DNA interaction. In this paper, the methodology of DNA-mediated computing is utilised to enrich decision theory, by demonstrating how a novel programmable DNA-mediated normative decision-making apparatus is able to capture rational choice under uncertainty.